2022
DOI: 10.21037/atm-22-3781
|View full text |Cite
|
Sign up to set email alerts
|

Bergenin inhibits palmitic acid-induced pancreatic β-cell inflammatory death via regulating NLRP3 inflammasome activation

Abstract: Background: Bergenin, an active constituent of plants of the genus Bergenia, has been reported to have antidiabetic properties. This study investigated whether bergenin is beneficial for treating type 2 diabetes mellitus (T2DM) via regulating NOD-like receptor family-pyrin domain containing 3 (NLRP3) inflammasome.Methods: Two pancreatic β-cell lines, INS-1 and MIN6, were treated with 1, 3, or 10 μM bergenin in the absence or presence of palmitic acid (PA). Cell Counting Kit (CCK)-8, flow cytometry, quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(56 reference statements)
1
2
0
Order By: Relevance
“…Apart from OS, inflammation and ERS have been demonstrated to be the significant factors for β-cell decline in T2DM 55 . In line with the previous study 29 , upregulated expression of the pro-inflammatory cytokines, TNF-α and IL-6, was observed in PA-induced MIN6 cells compared to normal cells. Significantly, 1,25(OH) 2 D 3 treatment reduced the expression of TNF-α and IL-6 in PA-induced MIN6 cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Apart from OS, inflammation and ERS have been demonstrated to be the significant factors for β-cell decline in T2DM 55 . In line with the previous study 29 , upregulated expression of the pro-inflammatory cytokines, TNF-α and IL-6, was observed in PA-induced MIN6 cells compared to normal cells. Significantly, 1,25(OH) 2 D 3 treatment reduced the expression of TNF-α and IL-6 in PA-induced MIN6 cells.…”
Section: Discussionsupporting
confidence: 92%
“…3c), suggesting the rescue of β-cell dysfunction. Inflammation has been demonstrated to be closely linked with β cell dysfunction, and PA can induce the release of pro-inflammatory mediators, such as tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6) [29]. As expected, PA-induced MIN6 cells had higher expression of TNF-α and IL-6 mRNAs than control cells, which were markedly reversed by 1,25(OH) 2 D 3 pretreatments (2 and 4 nM) in a dose-dependent way (p < 0.05; ▶Fig.…”
Section: Vitamin D Mitigates Pancreatic β-Cell Impairment In Vitromentioning
confidence: 99%
“…But other protein targets are implicated in the mechanism of action. Previous studies also suggested the binding of bergenin to the proteins NLRP3 (NOD-like receptor family-pyrin domain containing 3) inflammasome [129], antiapoptotic protein B-Cell Lymphoma 2 (Bcl-2) [130], enzyme galectin-3 [131] and several other proteins [132][133][134][135].…”
Section: Polyphenols and Flavonoidsmentioning
confidence: 94%
“…An array of different pharmaceuticals and nutriceuticals afford protection in pancreatic β-cells via the suppression of the NLRP3 inflammasome [ 176 , 177 , 178 ]. Although not investigated in pancreatic β-cells, melatonin suppresses the NLRP3 inflammasome in different cell types across the body [ 179 ], indicating another aspect to melatonin’s potential utility in T1DM treatment, as well as from locally produced pancreatic melatonin.…”
Section: Treatment Implicationsmentioning
confidence: 99%